THE GENDER SOCIALIZATION QUESTION IN EDUCATION: INFLUENCE ON BOYS’AND GIRLS’ACADEMIC ACHIEVEMENT - Kangethe, Ngigi S.; Lyria, Karuti S.; Nyamanga, Amutabi M. (European Scientific Journal, ESJ, 2014)
The present study explored secondary school students’ perception of gender identity (masculinity or femininity) and academic achievement. The relationship between these variables was measured. The study adopted descriptive survey design. Respondents included 500 students, 85 principals, 171 teachers, 92 parents and 8 education officers. The study shows that masculinity is generally perceived as lack of emotions and affections, while femininity as beauty conscious and marriage oriented. These perceptions shape attitudes and behaviour in schools, ultimately impacting negatively on academic achievement. The study made important findings that will inform interventions meant to equip boys and girls with skills to enable them balance gender traits in a manner that does not subjugate the innate biological sexual traits.